Answer:
2377.38 pounds of the first alloy
2773.62 pounds of the second alloy
Explanation:
First, let Alloy1 represent the alloy with 49% copper, Alloy2 the alloy with 62%, and Alloy3 the alloy with 56%.
The third alloy is made from a mixture of the first two, so:
MassAlloy1 + MassAlloy2 = MassAlloy3
MassAlloy1 + MassAlloy2 = 5151 lb eq.1
- The mass of copper in each alloy can be expressed as:
MassCopper1 = MassAlloy1 * 0.49 eq.2
MassCopper2 = MassAlloy2 * 0.62 eq.3
MassCopper3 = MassAlloy3 * 0.56 eq.4
The problem tells us that MassAlloy3 = 5151 lb, thus the copper mass in the third alloy is:
MassCopper3 = 5151 lb * 0.56 = 2884.56 lb
- From the problem, we know that this amout of copper comes from both the first and second alloys, thus:
MassCopper1 + MassCopper2 = MassCopper3
MassCopper1 + MassCopper2 = 2884.56 lb eq.5
- We can rewrite eq. 5 using eq. 2 and eq.3 :
MassAlloy1 * 0.49 + MassAlloy2 * 0.62 = 2884. 56 lb eq.6
Eq. 1 and Eq. 6 give us a system of two equations and two unknowns, so we can solve it:
- In Eq. 1 we express MassAlloy1 in terms of MassAlloy2:
MassAlloy1 + MassAlloy2 = 5151 lb
MA1 = 5151 - MA2
- Then we put it into eq. 6:
MassAlloy1 * 0.49 + MassAlloy2 * 0.62 = 2884. 56 lb
(5151-MA2) * 0.49 + MA2 * 0.62 = 2884.56
2523.99 - 0.49MA2 + 0.62MA2 = 2884.56
0.13MA2 = 360.57
MA2 = 2773.62
- Finally we use the value of MassAlloy2 to calculate MassAlloy1 in eq.1:
MassAlloy1 + MassAlloy2 = 5151 lb
MassAlloy1 + 2773.62 lb = 5151 lb
MassAlloy1 =2377.38 lb